Effect of dental treatments on salivary immunoglobulin A of children with and without dental caries: A comparative study - P R Geetha Priya; Sharath Asokan; K Karthick; N Venugopal Reddy; V Arun Prasad Rao (Wolters Kluwer Medknow Publications, 2013)
Aim: To evaluate and compare the effect of dental treatment on the salivary immunoglobulin A (IgA) levels of children with and without dental caries. Materials and Methods: The study involved 30 children, among which 15 had caries and the other 15 were without caries. Salivary sample collection was done for all the children before dental treatment, and for the children with caries, the sampling was repeated 3-4 weeks after the dental treatment. The salivary IgA quantitation was done by enzyme-linked immunosorbent assay (ELISA), using Human IgA ELISA Quantitation kit, and the results were statistically analyzed by independent sample "t" test. Results:The salivary IgA level was significantly more in children with caries (13.07 ± 1.55 mg/100 ml) than in caries-free children (11.90 ± 1.58 mg/100 ml) in the pre-treatment phase. The salivary IgA level in children with caries was 13.52 ± 1.68 mg/100 ml in the post-treatment phase and it was not statistically different from the pre-treatment value. Conclusion: Mere quantitation of salivary IgA levels might have no reflection on the functional antibodies involved in caries process, and successful dental treatment alone does not alter the salivary IgA levels, suggesting a multifaceted approach to combat the cariogenic challenge.